Prehospital tranexamic acid in trauma patients: a systematic review and meta-analysis of randomized controlled trials - Acharya, Pawan; Amin, Aamir; Nallamotu, Sandhya; Riaz, Chaudhry Zaid; Kuruba, Venkataramana; Senthilkumar, Virushnee; Kune, Harika; Bhatti, Sandeep Singh; Sarlat, Iván Moguel; Krishna, Chekuri Vamsi; Asif, Kainat; Nashwan, Abdulqadir J.; et al. (Frontiers in Medicine, 2023)
Background Prehospital tranexamic acid (TXA) may hold substantial benefits for trauma patients; however, the data underlying its efficacy and safety is scarce. Methods We searched PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov from inception to July 2023 for all randomized controlled trials (RCTs) investigating prehospital TXA in trauma patients as compared to placebo or standard care without TXA. Data were pooled under a random-effects model using RevMan 5.4 with risk ratio (RR) and mean difference (MD) as the effect measures. Results A total of three RCTs were included in this review. Regarding the primary outcomes, prehospital TXA reduced the risk of 1-month mortality (RR 0.82, 95% CI 0.69–0.97) but did not increase survival with a favorable functional outcome at 6 months (RR 1.00, 95% CI 0.93–1.09). Prehospital TXA also reduced the risk of 24-h mortality but did not affect the risk of mortality due to bleeding and traumatic brain injury. There was no significant difference between the TXA and control groups in the incidence of RBC transfusion, and the number of ventilator- and ICU-free days. Prehospital TXA did not increase the risk of adverse events except for a small increase in the incidence of infections. Conclusion Prehospital TXA is useful in reducing mortality in trauma patients without a notable increase in the risk of adverse events. However, there was no effect on the 6-month favorable functional status. Further large-scale trials are required to validate the aforementioned findings. Systematic review registration PROSPERO (CRD42023451759).